Morbidity Profile of Under Five Children Residing in Barbote Village Development Committee of Ilam District of Eastern Nepal - Sharma, Khem Raj; Dawadi, Suyash; Upadhayaya, Pawan; Khanal, Vijay Kumar; Singh, Suman Bahadur (Birat Journal of Health Sciences, 2019)
Introduction: In 2017, the under five mortality rate in low-income countries was 69 deaths per 1000 live births–around 14 times the average rate in high-income countries. Children constitute a vulnerable group and the first five years can be considered as a transition phase from the mother’s womb to a social platform. Morbidity status of very young children is considered to be an important index of the health status of the community. However, studies done to assess the morbidity profile of Children in rural Nepal are few, and the children’s health status is largely unknown. The information collected through Health Management Information System (HMIS) of Nepal Government mainly represent the population that accessed the services but do not represent the population that utilized private clinics/hospitals or did not access it at all. Objective: This study was conducted to assess the morbidity status of under-five children and its associated factors in Barbote Village Development Commitiee (VDC) of Ilam district of eastern Nepal. Methodology: A community based cross-sectional study was conducted among all the eligible under five children of Barbote VDC of Ilam District for two weeks from 16-30 March, 2016. Face-to-face interviews were conducted with the legal guardian/ caretaker of the children with pre-tested, semi-structured questionnaire. Calibrated & validated equipment were used for simple biophysical measurements. Odds Ratio (OR) with confidence limit was calculated to examine the strength of association between the variables with the probability of significance set at 95% of Confidence interval (CI).Ethical permission was taken from the Institutional Review Committee (IRC) of BP Koirala Institute of Health Sciences, Dharan. Results: Of the total 406 under-five children studied, 35.5% complained of illness such as acute respiratory infection, diarrhea and fever within the past two weeks. Regression analysis by the backward conditional method disclosed the fact that children of households with low socioeconomic status and those using biomass fuel for cooking were significantly associated with presence of illness. Conclusion: More than one-third of the under-five children in BarboteVDC of eastern Nepal were found to be ill mostly due to preventable causes. Factors significantly associated with the presence of illness included the use of biomass fuel and low socio-economic status.